2018
DOI: 10.3390/ijms19092595
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Type Identification of Self-Incompatibility in Dendrobium and Its Phylogenetic Evolution Pattern

Abstract: Self-incompatibility (SI) is a type of reproductive barrier within plant species and is one of the mechanisms for the formation and maintenance of the high diversity and adaptation of angiosperm species. Approximately 40% of flowering plants are SI species, while only 10% of orchid species are self-incompatible. Intriguingly, as one of the largest genera in Orchidaceae, 72% of Dendrobium species are self-incompatible, accounting for nearly half of the reported SI species in orchids, suggesting that SI contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…Among those barcoding regions, ITS was the most commonly used. [2,8,9,14,15,25,[36][37][38][39]. Our results again confirmed the effect of ITS in the evaluation of genetic diversity and the identification of Dendrobium species not only in Southern Vietnam but also in other habitats.…”
Section: Discussionsupporting
confidence: 81%
“…Among those barcoding regions, ITS was the most commonly used. [2,8,9,14,15,25,[36][37][38][39]. Our results again confirmed the effect of ITS in the evaluation of genetic diversity and the identification of Dendrobium species not only in Southern Vietnam but also in other habitats.…”
Section: Discussionsupporting
confidence: 81%
“…The typical GSI reactions that can lead to PCD in pollen tubes are based on S-RNase proteins in the pistil and F-box proteins in the microgametophyte in Solanaceae [ 5 , 38 , 39 ] as well as a Ca 2+ -dependent signaling cascade in Papaveraceae [ 40 ]. In the case of self-incompatible Orchidaceae species, molecular studies have not revealed the presence of S-RNases, suggesting that a distinct molecular control of GSI could occur in the family [ 41 , 42 ]. Additionally, there are no records involving a Ca 2+ -dependent signaling cascade in the death of pollen tubes in Orchidaceae.…”
Section: Discussionmentioning
confidence: 99%
“…SI-related patents have also been issued in species with unknown SI genetics. For instance, Dendrobium species are of interest as ornamental and medicinal plants, but show a high rate of SI and the system has not been characterized (Niu et al, 2018). Thus, in Dendrobium officinale (Orchidaceae) a method has been patented for overcoming SI using a pollination accelerator based on indole acetic acid (Xin et al, 2017).…”
Section: Patented Applications Of Plant Si Systemsmentioning
confidence: 99%